Zingiber officinale: a natural gold - A. K. GHOSH; S. BANERJEE; H. I. MULLICK; J. BANERJEE (International Journal of Pharma and Bio Sciences, 2011)
Ginger, (Zingiber officinale Roscoe, Zingiberacae) is one of the important medicinal plant which naturally occurs in various country like India, China, South East Asia, West Indies, Mexico and other parts of the world. This natural gold has been consumed worldwide as a spice and flavoring agent from the ancient time. Ginger plants are generally 1-3 ft. in height and having different chemical constituents like Amaldehyde, Gingerol, Shogaol, and Paradol etc. It has some tremendous beneficial effect to human body to cure various types of diseases. Ginger bears an enormous number of pharmacological activities among those, Neuro-protective activity and activity against colon cancer have facilitated the extent of further research for finding out less toxic and more potent drugs for the better treatment of those diseases. This review will facilitate to gain all about the past scientific research and the necessary information about the enormous pharmacological activities of ginger which will insist researchers for future research to protect human beings from several types of diseases and may serves as a natural gold for the promotion of mankind.